Taxonomic notes on the Chinese endemic genus Straneostichus Sciaky, 1994 (Coleoptera: Carabidae: Pterostichini), with descriptions of three new species - Chen, Jia-Heng; Shi, Hong-Liang; Liang, Hong-Bin (Zootaxa, 2022)
A total of eleven species and two subspecies are recognized within the Chinese endemic genus Straneostichus Sciaky, 1994 (Carabidae: Pterostichini), including three new species described in the present paper: Straneostichus politus sp. nov. (Sichuan: Wolong), Straneostichus liupanensis sp. nov. (Ningxia: Liupanshan) and Straneostichus ganqingensis sp. nov. (Qinghai: Mengda and Gansu: Dangchang). Taxonomical notes and new distribution records for all the known species are provided, along with an updated key to the species of Straneostichus.